Qualidade fisiológica de sementes de soja tratadas com fungicida e recobertas com polímeros - Benatto Junior, João Carlos (2008)
The use of polymers in soybean seeds has been accomplished with the purpose of incorporating products like insecticides, fungicides, growing substances, minor fertilizers and so on, in order to improve the visual aspect of the seed, to promote smaller operator's intoxication risk and to provide a better seeds' acting and seedlings after sowing. The main objective of this work was to evaluate the recovered seeds' effects in soybeans seed quality lots of high and low germination of the cv. AG 7000. The seed's film coating was accomplished with two commercial marks of polymers, LABORSAN ® , and LANXESS ® , in doses of 2 and 3,5 ml for each kg with and without mixture of the fungicide Carbendazim + Thiram (firewalk ® ). The seeds' quality evalutions, were measured by the germination test, germination in sand and accelerated aging. The use of polymers in soybean seeds provides seeds with good appearance and coloration and can be applied to differentiate the seed from the commercial grain. The fungicide and the polymers do not affect the physiological quality of soybean seed. The results of the polymers and fungicide were superior in the test of accelerated aging, showing higher germination in relation to the check treatment.